Environmental management towards sustainability - Modak, Prasad (Boca Raton : Taylor & Francis, 2018)
'The book provides the reader a deeper understanding on environmental management and concerns regarding sustainability of the planet. In explaining the issues,'nexus' between issues is emphasized that is generally missed in most of the books with examples and visuals' --
Challenges we face today -- Response from the national governments -- Financial institutions -- Business response -- Responses by business sectors -- Community response.
'A CRC title, part of the Taylor & Francis imprint, a member of the Taylor & Francis Group, the academic division of T&F Informa plc' -- Title page.
Includes bibliographical references and index.
Keywords: Sustainable development; Environmental management; Social responsibility of business